A case of transverse colon cancer with a large liver abscess that could be treated with a radical operation after infection control. (2020) - Kogo, Hideki; Yamamoto, Kazuhito; Yoshida, Hiroshi
Highlights: Advanced colorectal cancer is known to be associated with liver abscesses. A strategy to treat liver abscesses as early as possible is necessary to prevent worsening nutritional status of the patient for surgery. Prompt drainage of liver abscesses is essential in patients with colorectal cancer complicated by liver abscesses that require early surgery. Abstract: Introduction: Advanced colorectal cancer is known to be associated with liver abscesses. A strategy to treat liver abscesses as early as possible is necessary to ensure high surgical curability before the cancer progresses and to prevent worsening nutritional status of the patient during surgery. Presentation of case: An 82-year-old woman was hospitalized due to fever. A 10 cm in diameter liver abscess and advanced colon cancer were diagnosed. After conservative treatment of the liver abscess with antibiotics and puncture drainage, colorectal cancer surgery was performed on a standby basis. Discussion: We propose that empiric antibiotic therapy should be administered early in cases of liver abscesses that may require early colorectal surgery. Abscess drainage should be performed promptly if the abscess is of a size that can be punctured easily. Conclusion: In patients with advanced colorectal cancer complicated by liver abscesses that required early surgery, prompt drainage of the liver abscesses is mandatory.